Leveraging Digital Audits and Collaborative Team Support to Optimize Auditor Performance - Muhaimin, Muhaimin; Fanani, Zainal; Tjaraka, Heru (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Purpose: This study examines the relationship between team support, management support, and digital audit on auditor performance. It also investigates the role of management support in strengthening the effect of team support on auditor performance within digital audit environments. Research Design and Methodology: The study employs a quantitative approach with primary data collected through questionnaires distributed to auditors. Using a correlational and cross-sectional design, data were analyzed with Structural Equation Modeling (SEM) using PLS 4.0 to assess the relationships among variables. Findings and Discussion: The results show that digital audits significantly improve auditor performance, highlighting that digital technology enhances audit accuracy and efficiency. Team support positively affects both management support and auditor performance, as collaboration encourages management to provide necessary resources and training. Additionally, management support directly improves auditor performance and mediates the relationship between team support and auditor performance, indicating that team effectiveness increases when supported by management. Implications: This study contributes to understanding auditor performance in digital audits and emphasizes the importance of team and management collaboration. The findings suggest that organizations should enhance team cohesion and management support to optimize auditor performance, and further research on digital audit implementation should be recommended.